Superstitious beliefs of the intermediate grade pupils of Northern Luzon Teachers College Laboratory School and their implications for health education in grade five and six - Abara, Deborah R. 1921- (1964)
This study surveys and explains the prevalence of the common superstitious beliefs among children. Implications, scientific bases and explanations of the erroneousness of superstitious beliefs are presented in this study so that they may be used as resource materials in developing instructional units in health education for grades five and six pupils.